Four new species of Heilus Kuschel 1955 (Curculionidae, Molytinae, Molytini, Hylobiina) from Brazil - Lira, Aline De Oliveira; Sousa, Wesley Oliveira De; Marques, Marinêz Isaac (Zootaxa, 2023)
Four new species, namely Heilus rosadonetoi Lira, De Sousa & Marques sp. nov., Heilus christinae Lira, De Sousa & Marques sp. nov., Heilus vanini Lira, De Sousa & Marques sp. nov., and Heilus obrieni Lira, De Sousa & Marques sp. nov., are described from Brazil. The new species are illustrated with habitus photographs and drawings of male and female genitalia. The present study expands the diversity of the genus Heilus to include 22 species in the Neotropical region, with the highest number of species (16 species) distributed in Brazil.